RNA-Seq of Guar (Cyamopsis tetragonoloba, L. Taub.) Leaves: De novo Transcriptome Assembly, Functional Annotation and Development of Genomic Resources - Tanwar, Umesh K.; Pruthi, Vikas; Randhawa, Gursharn S. (Frontiers in Plant Science, 2017)
Genetic improvement in industrially important guar (Cyamopsis tetragonoloba, L. Taub.) crop has been hindered due to the lack of sufficient genomic or transcriptomic resources. In this study, RNA-Seq technology was employed to characterize the transcriptome of leaf tissues from two guar varieties, namely, M-83 and RGC-1066. Approximately 30 million high-quality pair-end reads of each variety generated by Illumina HiSeq platform were used for de novo assembly by Trinity program. A total of 62,146 non-redundant unigenes with an average length of 679 bp were obtained. The quality assessment of assembled unigenes revealed 87.50 % of complete and 97.18 % partial core eukaryotic genes (CEGs). Sequence similarity analyses and annotation of the unigenes against non-redundant protein (Nr) and Gene Ontology (GO) databases identified 175,882 GO annotations. A total of 11,308 guar unigenes were annotated with various enzyme codes (EC) and categorized in six categories with 55 subclasses. The annotation of biochemical pathways resulted in a total of 11,971 unigenes assigned with 145 KEGG maps and 1,759 enzyme codes. The species distribution analysis of the unigenes showed highest similarity with Glycine max genes. A total of 5,773 potential simple sequence repeats (SSRs) and 3,594 high-quality single nucleotide polymorphisms (SNPs) were identified. Out of 20 randomly selected SSRs for wet laboratory validation, 13 showed consistent PCR amplification in both guar varieties. In silico studies identified 145 polymorphic SSR markers in two varieties. To the best of our knowledge, this is the first report on transcriptome analysis and SNPs identification in guar till date.